Economic valuation of the nipa industry in Mauban, Quezon. - Tribiana, Norris T. (2014)
The study was able to determine the value of the nipa industry in Barangay Bagong Bayan Mauban, Quezon using Cost Benefit Analysis (CBA). On the other hand, soil samples and geographical coordinates were obtained from each sampling site. The environmental factors were measured and questionnaires were administered to the 40% of the stakeholders. The necessary data for knowledge and awareness and CBA were obtained through the questionnaires. The environmental factors affecting the Nypa fruticans such as soil temperature, soil pH, humidity, and light were correlated to the abundance of Nypa fruticans in the area. The knowledge and awareness of the stakeholders were also determined. Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR) are the determining factors for CBA. Based on the results, the nipa industry in Barangay Bagong Mauban, Quezon is valuable and beneficial to the stakeholders because the value of NPV, BCR and IRR agrees with the decision rule. For knowledge and awareness, the stakeholders do not have knowledge to the statements administered to them. In awareness, they are aware about the potential and capabilities of Nypa fruticans. Results also show that the answers of the stakeholders for awareness and knowledge have significant difference. For the environmental factors, all of the environmental factors that were correlated show no significant relationship with the abundance of Nypa fruticans.